Quantitative assessment of crop residues in no-till technology according to remote sensing data and field soil cover survey - N. R. Ermolaev; S. A. Yudin; V. P. Belobrov; V. K. Drediger; R. G. Gadzhiumarov (Бюллетень Почвенного института им. В.В. Докучаева, 2022)
The key feature of the no-till technology is the preservation of crop residues on the soil surface. Crop residues quantitative assessment is an important task when introducing technology into production. On the basis of field and remote sensing data, different approaches to this assessment are considered. The research was carried out in the Budennovsky district of the Stavropol Territory in the fields of farms using both traditional technology (TT) and no-till (ПП). Images of the Sentinel-2 system were used as remote sensing data, on the basis of which the spectral indices NDTI and NDVI were calculated. Three methods were used to estimate the projective cover by plant residues: 1) weight accounting of plant residues per unit area; 2) field determination of the projective cover by the method of line transects; 3) desk analysis of photographs of the soil surface. Based on the obtained results, models of the linear dependence of NDTI values on the projective cover of the soil surface with plant residues were constructed. The possibility of quantitative accounting of plant residues only on the basis of remote sensing data was also analyzed. The highest coefficient of determination (R2 = 0.97) with the smallest square root of the standard error (RMSE = 7.93) was obtained by modeling based on the analysis of photographs of the soil surface covered with plant residues. Based on the model of the dependence of NDTI values on the projective cover of plant residues obtained as a result of the analysis of photographs based on Sentinel -2 satellite data for the growing season 2020–2021, data were obtained on the dynamics of soil coverage with plant residues (CRC) on the scale of a single field an d different tillage technologies. As an approbation of the approach and an assessment of its use for solving production problems, the dynamics of the projective cover with plant residues was analyzed under different crops and different relief conditions. An analysis of the dynamics of CRC values made it possible to distinguish between different stages of crop cultivation under traditional technology (TT) and no-till (ПП), and also on the scale of an individual field revealed the heterogeneity of the projective soil cover with plant residues associated with the features of the mesorelief.